2010
DOI: 10.1007/s00216-010-4161-2
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of certified calibration solutions for azaspiracid-1, -2, and -3, potent marine biotoxins found in shellfish

Abstract: 1 AbstractThe production and certification of a series of azaspiracid (AZA) calibration solution reference materials is described. Azaspiracids were isolated from contaminated mussels, purified by preparative liquid chromatography and dried under vacuum to the anhydrous form. Purity was assessed by liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR) spectroscopy. Final concentration of each AZA in a CD 3 OH stock solution was determined accurately by quantitative NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…The use of ethanol as an extraction solvent for the purification of azaspiracids has previously been reported. 33 Small scale tests with methanol and ethanol as extraction solvents showed that both solvents were equivalent in terms of extraction efficiency. Ethanol was chosen as the extraction solvent primarily to minimize the formation of side products, which can be significant when methanol is used as an extractant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The use of ethanol as an extraction solvent for the purification of azaspiracids has previously been reported. 33 Small scale tests with methanol and ethanol as extraction solvents showed that both solvents were equivalent in terms of extraction efficiency. Ethanol was chosen as the extraction solvent primarily to minimize the formation of side products, which can be significant when methanol is used as an extractant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As such, many of the previous SAR studies have been confined to the study of AZA1 and its synthetic fragments (43,44); however, purified AZA2 and AZA3 have recently become available commercially (45).…”
Section: Acs Paragon Plus Environment Chemical Research Inmentioning
confidence: 99%
“…The aliquot had been set aside after NMR-characterization of the whole lot and was stored in methanol at −80 °C, a condition under which no degradation of AZA1 was observed during a 12-month stability study (Perez et al, 2010). The isolation procedure has been briefly described by Ronzitti et al (2007).…”
Section: Methodsmentioning
confidence: 99%